A time-motion analysis of international women`s water polo match play - D`Auria, S.; Gabbett, T. J. (International Journal of Sports Physiology and Performance, 2008)
Purpose: The purpose of this study was to investigate the physiological demands of field players in international women`s water polo match play. Methods: Video footage was collected at the 13th FINA Women`s Water Polo World Cup in Perth in 2002. Video recordings were analyzed using a simple hand-based notation system to record predefined activity durations, frequencies, and corresponding subjective intensities. Results: Average exercise bout duration was 7.4 ± 2.5 s and exercise to rest ratio within play 1:1.6 ± 0.6. The average pattern of exercise was represented by 64.0 ± 15.3% swimming, 13.1 ± 9.2% contested swimming, 14.0 ± 11.6% wrestling, and 8.9 ± 7.1% holding position. Significant differences existed between outside and center players for percentage time swimming (67.5 ± 14.0% vs 60.2 ± 13.3%, P = .002) and wrestling (9.9 ± 9.3% vs 18.4 ± 11.1%, P = .000). A significant difference was found in the number (P = .017) and duration (P = .010) of high-intensity activity (HIA) bouts performed each quarter for outside (1.8 ± 2.2 bouts, 7.0 ± 3.4 s) and center players (1.2 ± 1.5 bouts, 5.2 ± 3.4 s). Positional differences in HIA were the result of a significant difference (P = .000) in the number of maximal/near maximal swims (outside 1.2 ± 1.5 and center 0.5 ± 0.9 per quarter). Conclusions: This study characterizes international women`s water polo match play as a highly intermittent activity. Swimming, particularly high intensity, has greater significance to outside players, whereas wrestling has greater significance to center players.